2021
DOI: 10.1177/1534734621990311
|View full text |Cite
|
Sign up to set email alerts
|

Dermal Matrices: Game Changers in Leg and Foot Soft Tissue Reconstruction? A Case Series

Abstract: The present article aims to present the use of dermal matrices in severe degloving, avulsion, and necrotizing injuries of the leg and foot in 3 patients. Conventional reconstruction would require the use of free flaps, since exposure of vessels, nerves, joints, and tendons rendered the mere resurfacing with skin grafts insufficient, and extensive cutaneous detachment precluded the use of local fasciocutaneous flaps. All injuries underwent thorough and repeated surgical debridements and wash outs, followed by n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 21 publications
(178 reference statements)
0
7
0
Order By: Relevance
“…Recently, studies showing a high success rate when combined treatment with dermal matrix and NPWT were performed before skin grafting were published 8–10 . It has been reported that NPWT can accelerate the integration of artificial dermis into the wound bed and provide controlled continuous or intermittent subatmospheric pressure 10 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, studies showing a high success rate when combined treatment with dermal matrix and NPWT were performed before skin grafting were published 8–10 . It has been reported that NPWT can accelerate the integration of artificial dermis into the wound bed and provide controlled continuous or intermittent subatmospheric pressure 10 .…”
Section: Discussionmentioning
confidence: 99%
“…If the combination treatment using NPWT dressing on the artificial dermis suggested in our study can be applied to cover the exposed bone, tendon, and hardware structures with granulation tissue, STSG can be possible. In these cases, using STSG compared with flaps provides certain advantages, including technical autonomy of the vascular anatomy, early wound closure with minimal donor site morbidity, and the possibility of other options for later reconstruction 8 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations